1991
DOI: 10.1039/ft9918700215
|View full text |Cite
|
Sign up to set email alerts
|

Packing schemes for Lennard-Jones clusters of 13 to 150 atoms: minima, transition states and rearrangement mechanisms

Abstract: Clusters of 13-150 Lennard-Jones atoms have been investigated, with attention given to clusters at both 'magic' and intermediate nuclearities. Icosahedral, decahedral and face-centred-cubic structures are compared in terms of their relative energies and the topology of the potential-energy surfaces. In particular, both gradient and second-derivative optimisation schemes are employed, and all structures are characterised in terms of their force constants. W e find a number of interesting relationships between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 33 publications
1
21
1
Order By: Relevance
“…We call a cluster "Gregory-Newton" (GN) when it belongs to the set of all clusters consisting of 12 spheres kissing a central sphere. The canonical Gregory-Newton cluster is the icosahedron, which is perhaps the most common form studied in cluster chemistry and physics [2,41,65,66]. We therefore investigate this cluster type in more detail here.…”
Section: The Special Case Of a Gregory-newton Clustermentioning
confidence: 99%
“…We call a cluster "Gregory-Newton" (GN) when it belongs to the set of all clusters consisting of 12 spheres kissing a central sphere. The canonical Gregory-Newton cluster is the icosahedron, which is perhaps the most common form studied in cluster chemistry and physics [2,41,65,66]. We therefore investigate this cluster type in more detail here.…”
Section: The Special Case Of a Gregory-newton Clustermentioning
confidence: 99%
“…11,[15][16][17] Morphology interconversion processes have been studied for monometallic, core-shell and vertex-decorated systems by means of transition state search algorithms, molecular dynamics or enhanced sampling techniques. [18][19][20][21][22][23][24][25][26][27][28] It has been shown that solidsolid transitions of cuboctahedral (Co) or decahedral (Dh) morphologies into icosahedral (Ih) one happens in nanoclusters, with sizes as small as 147 atoms, via cooperative screw-dislocation motions also known as diamond-square-diamond (DSD) rearrangements. 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…The model process keeps connected units connected, forbids geometric overlap of units (volume exclusion) and connects randomly chosen units if geometrically permitted. Based only on such random monomer interactions and geometric constraints, akin to those in Lennard-Jones clusters and sticky hard spheres [37,38], the 3D structures self-organizing through the simple model process are consistent with those of real protein ensembles in all of the above-mentioned features simultaneously.…”
Section: Introductionmentioning
confidence: 84%